The Study of Sociological Effective Factors on Social Trust (A Case Study: Female Students in Abdanan Payam-Noor University) - jaber molaii; ali ranjbarian; seyed ali seyedi; seyed aliakbar hosseini (توسعه اجتماعی)
Creating trust and trust increase are considered inevitable and significant in the field of training human resources us well as human heritage in our country. This ciological research has dealt with female university students’ social trust- the study data were obtained with a descriptive method through a sample of 253 subjects from among 748 female students in Payame Noor University of Abdanan city. The sampling has been in a random selection way. The results of the study revealed that there is relationship between social-economic basis of family, life enjoyment and satisfaction, altruism, social security feeling, religious beliefs, social acceptability and social trust the independent variables have experimented 52 percent of the social trust changes. Totally, the results show that the amount of Payame Noor University of Abdanan female students’ social trust is average and lower than average.